2016
DOI: 10.6061/clinics/2016(02)08
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of urethral injection therapy for urinary incontinence in women: a systematic review

Abstract: To evaluate the efficacy and safety of different bulking agents for treating urinary incontinence in women, a systematic review including only randomized controlled trials was performed. The subjects were women with urinary incontinence. The primary outcomes were clinical and urodynamic parameters. The results were presented as a weighted mean difference for non-continuous variables and as relative risk for continuous variables, both with 95% confidence intervals. Initially, 942 studies were identified. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(35 reference statements)
0
18
0
1
Order By: Relevance
“…Many agents have been introduced to the market and since removed due to clinical concerns or marketing reasons. 5 Polyacrylamid hydrogel (PAHG, Bulkamid™) is the only injectable bulking agent currently approved and marketed in Canada with an indication for female SUI. Non-animal hyaluronic acid/dextranomer gel (NASHA/Dx) was previously available and marketed with an Implacer device as Zuidex™; 6 however, concerns were raised regarding its efficacy and development of sterile abscesses with this product, and it was not approved in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Many agents have been introduced to the market and since removed due to clinical concerns or marketing reasons. 5 Polyacrylamid hydrogel (PAHG, Bulkamid™) is the only injectable bulking agent currently approved and marketed in Canada with an indication for female SUI. Non-animal hyaluronic acid/dextranomer gel (NASHA/Dx) was previously available and marketed with an Implacer device as Zuidex™; 6 however, concerns were raised regarding its efficacy and development of sterile abscesses with this product, and it was not approved in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review looking at complications of urethral bulking agents in over 1800 women suggests that most adverse effects are minor and transient, with urinary retention and infection being the most common . A further review of over 6000 cases by de Vries et al reported an overall complication rate of 32%, with most complications being minor and transient.…”
Section: Treatment Of Stress Urinary Incontinencementioning
confidence: 99%
“…However, their long-term (greater than 15 months) economic viability is questionable when compared with that of traditional sling surgery for SUI ( 35 ). Common complications following the injection of IBAs include urinary retention (up to 30%) and urinary tract infection (up to 25%) ( 38 ). Rare complications include abscess formation following collagen injection and fat embolism after autologous fat injection ( 38 ).…”
Section: Stress Urinary Incontinencementioning
confidence: 99%
“…Common complications following the injection of IBAs include urinary retention (up to 30%) and urinary tract infection (up to 25%) ( 38 ). Rare complications include abscess formation following collagen injection and fat embolism after autologous fat injection ( 38 ).…”
Section: Stress Urinary Incontinencementioning
confidence: 99%